Comparing Flow Cytometry QBeads PlexScreen Assays with Other Immunoassays for Determining Multiple Analytes. (August 2018) - Ding, Mei; Cavallin, Anders; Hermansson, Nils-Olov; Berntsson, Pia; Jinton, Lisa; Rodrigo Blomqvist, Sandra
Immunoassays, utilizing the affinity of antibodies to their antigens, are powerful techniques and have been widely used for quantifying analytes, such as cytokines, in biological samples in the clinic and in drug discovery. Various immunoassays have been developed to fit for different purposes. Recently, bead-based flow cytometry assays have emerged as interesting options for multiplex quantification of analytes. In this study, we compared high-throughput flow cytometry multiplex iQue QBeads PlexScreen assays with several other commonly used immunoassays, including MSD, Luminex, ELISA, HTRF, and AlphaLISA assays. Head-to-head comparisons of quantification data of the following cytokines were made: (1) IL-2, IL-4, IL-6, IL-13, IL-17A, IFNγ, KC/GRO, RANTES, and TNFα in mouse bronchoalveolar lavage fluid samples; (2) IL-10 and TNFα in supernatants from a THP-1 cell assay; (3) IL-6, IL-10, IL-12p70, and TNFα in supernatants from a human monocyte-derived dendritic cell assay; and (4) IL-2 in supernatants from a human CD4+ cell assay. The results demonstrated a good assay correlation between the iQue and the compared assays for the cytokine studied. Although overall good assay correlations were observed, our results showed that the iQue assay generated different absolute cytokine values for some cytokines in the same sample sets compared with other assays.